2023
DOI: 10.1097/js9.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes of modified laminoplasty with preservation of muscle group inserted into C2 and C7 spinous processes versus conventional C3–C7 laminoplasty: a prospective, randomized, controlled, noninferiority trial

Abstract: Background: The efficacy and noninferior of performing modified double-door laminoplasty (MDDL) (C4–C6 laminoplasty plus C3 laminectomy, alongside a dome-like resection of the inferior part of the C2 lamina and the superior part of the C7 lamina) in patients with multilevel cervical spondylotic myelopathy (MCSM) is equivocal. A randomized, controlled trial is warranted. Objective: The objective was to evaluate the clinical efficacy and noninferior of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 1 Research has shown that cervical muscle strength is associated with axial symptoms 2 and preservation of the muscles attached to the C2 spinous process may potentially reduce the incidence of axial pain. 3 , 4 In addition, minimally invasive atlantoaxial surgery offers a significant number of advantages, including protection of the suboccipital muscles, reduced bleeding, shorter hospital stay, reduced reliance on pain medication, and no significant increase in complications. 5 Recent studies have reported minimally invasive atlantoaxial fusion procedures performed percutaneously using intraoperative CT navigation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Research has shown that cervical muscle strength is associated with axial symptoms 2 and preservation of the muscles attached to the C2 spinous process may potentially reduce the incidence of axial pain. 3 , 4 In addition, minimally invasive atlantoaxial surgery offers a significant number of advantages, including protection of the suboccipital muscles, reduced bleeding, shorter hospital stay, reduced reliance on pain medication, and no significant increase in complications. 5 Recent studies have reported minimally invasive atlantoaxial fusion procedures performed percutaneously using intraoperative CT navigation.…”
Section: Introductionmentioning
confidence: 99%